2013
DOI: 10.1590/s1517-86922013000500010
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do treinamento concorrente e destreinamento sobre o biomarcador anti-inflamatório e níveis de condicionamento físico em crianças obesas

Abstract: Objective: To examine the effect of 12 weeks of (3 days/week) concurrent training and 4 weeks of detraining on serum adiponectin concentrations and physical fitness levels in obese boys without dietary intervention. Methods: 24 healthy boys, 11-13 years old with body mass index >28 voluntarily participated in the study. They were divided into two groups, experimental (n = 12) and control (n = 12). results: Adiponectin concentrations after 12 weeks presented significant decline in both experimental and control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…It is probable that the experimental diet interfered more in muscle adaptation than the CT protocol, since animals fed the hypercaloric diet (OS and OE) demonstrated a significant increase (p <0.05) compared to the other groups of animals (GS and GE). Fazelifar et al (2013), observed the effects of CT in obese children. It was found that the protocol used was sufficient to develop increased physiological variables of VO2 max, flexibility and strength.…”
Section: Discussionmentioning
confidence: 99%
“…It is probable that the experimental diet interfered more in muscle adaptation than the CT protocol, since animals fed the hypercaloric diet (OS and OE) demonstrated a significant increase (p <0.05) compared to the other groups of animals (GS and GE). Fazelifar et al (2013), observed the effects of CT in obese children. It was found that the protocol used was sufficient to develop increased physiological variables of VO2 max, flexibility and strength.…”
Section: Discussionmentioning
confidence: 99%
“…The different studies carried out in children or adolescents with obesity indicate that the adiponectin response to exercise depends on the different hormonal changes associated with sex in the pre-or postpubertal age [19]. In this sense, Fazelifar et al [301] observed a decrease in adiponectin levels compared to baseline in both study groups after 12 weeks of concurrent training or the maintenance of daily usual activities (control group). However, after four weeks of detraining, adiponectin levels did not increase in the experimental group despite gradual deconditioning.…”
Section: The Role Of Physical Activity In Adipokinesmentioning
confidence: 99%